Perbandingan antara Etika Jürgen Habermas dan Richard Rorty sebagai Prinsip Dasar Bertindak Manusia - Dominique Rio Adiwijaya (Bina Nusantara University, 2010)
Ethics without doubt is an issue in every scientific field. Questions on ethics are not merely questions on the responsibility of one or two specific individuals, but rather as what have been defined accurately by Immanuel Kant in Critique of Practical Reason – as question of all humanity as a thinking creature and the freedom of choice on, “what should I do”. From Kant’s definition, we may infer that if human can not think and not free in determining their choice, it would be almost impossible to hope for moral responsibility. However this article does not mean to give a full and historical description on ethics, but a sketch on discourse of contemporary ethics which is represented by two famous philosophers, Jürgen Habermas from the tradition of Critical Theory from Frankfurt School, dan Richard Rorty with “Neo-Pragmatism”. Habermas proposes “discourse ethics” while Rorty proposes ethic concepts through his “liberal-ironists”. It is hoped that the assembly of readers may gain an insight of the unavoidable ethics problems since every ethical position must be theory laden and the theory itself has historical characteristics (the characteristics, origin and historical context of the schools behind it). Therefore ethics is a neverending reflection although it has been started from 2500 years ago. Ethics invites us from specific sciences to enter its general discourse which unavoidably all-encompassing in its nature.